First Comprehensive Characterization of Phayre’s Leaf-Monkey (Trachypithecus phayrei) Karyotype - Fan, Xiaobo; Pinthong, Krit; de Oliveira, Edivaldo H. C.; Tanomtong, Alongklod; Chen, Hongwei; Weise, Anja; Liehr, Thomas (Frontiers in Genetics, 2022)
The chromosomal homologies of human (Homo sapiens—HSA) and Trachypithecus phayrei (TPH—Phayre’s leaf-monkey, family Cercopithecidae) have previously been studied by using classical chromosome staining/banding and fluorescence in situ hybridization (FISH) from the 1970s to 1990s. In this study, we carried out molecular cytogenetics applying human multicolor banding (MCB), locus-specific, and human heterochromatin-specific probes to establish the first detailed chromosomal map of TPH, which was not available until now. Accordingly, it was possible to precisely determine evolutionary-conserved breakpoints (ECBs) and the orientation of evolutionary-conserved segments compared to HSA. It could be shown that five chromosomes remained completely unchanged between these two species, and 16 chromosomes underwent only intrachromosomal changes. In addition, 50 ECBs that failed to be resolved in previous reports were exactly identified and characterized in this study. It could also be shown that 43.5% of TPH centromere positions were conserved and 56.5% were altered compared to HSA. Interestingly, 82% ECBs in TPH corresponded to human fragile sites. Overall, this study is an essential contribution to future studies and reviews on chromosomal evolution in Cercopithecidae.